Evidence-Based Management of Hypertension. (March 2011) - Rossi, GP; Weir, Matthew R
Synopsis: The following features contribute towards making Evidence-Based Management of Hypertension a remarkable book: authors who are recognized experts in their fields provide updated comprehensive information on many aspects of the complex management of arterial hypertension; compilation of the chapters was according to the criteria of evidence-based medicine, thus critically selected yet scientifically correct data are provided; and it can be used by practicing physicians to address issues they might face in their clinical practice, but also by experts for preparation of lectures for a wide range of scientific audience.